Effect of L-carnitine, Multivitamins and their Combination in the Treatment of Idiopathic Male Infertility - Jehan J. Aram; Kassim J. Al-Shamma; Ansam N. Al-Hassani (College of Pharmacy University of Baghdad, 2017)
The aim of the present study is to investigate and compare the efficacy of L-carnitine, multivitamins and their combination therapies on semen characteristics in idiopathic male infertility. Idiophathic infertile patients were randomly divided into three groups who had received three different treatment regimens for three months: group A (45 patients) has received 2 grams daily of L-carnitine alone; group B (55 patients) had received the combination of  L-carnitine (2 grams daily) plus one tablet daily of multivitamins (StresstabsÂ®); and group C (29 patients) had received one tablet daily of multivitamins alone. The study was started on 1/11/2009 and completed on 31/3/2010 and performed at Rizgari Teaching Hospital in Hawler City/Erbil Governorate. Thirty fertile male volunteers were used as a control group as well. Seminal fluid analysis has been done before treatment and then monthly after treatment for three month. The results of the present study clearly demonstrated that the combination therapy of L â€" carnitine and multivitamins was more efficient than each drug therapy alone and this evidenced by improvement and significant increase in the semen parameters; sperm concentration (72%), sperm count (79%), actively motile sperm (29%), and progressive motile sperm count (125%) when compared to pretreatment values than either L â€" carnitine or multivitamins therapy alone (53%, 60%, 19% and 84%), (21%, 30%, Non Significant, 34%) respectively.The results demonstrated that the combination therapy of L-carnitine and multivitamins was more efficient and produced more significant improvement in semen characteristic than either therapy alone, and that L-carnitine therapy was more efficient than multivitamins.Improvement in these semen parameters can aid in the treatment of idiopathic male infertility. Key words : L-carnitine, multivitamins, infertility.